Retrospective Analysis of Clinical Attributes Related to Uterine Torsion in Goats - Baria, Vishnu R.; Chauhan, Prakash M; Suthar, Babulal N; Patel, Ramesh M; Prajapati, Ankit S (Indian Journal of Veterinary Sciences and Biotechnology, 2023)
The retrospective analysis of clinical attributes and incidence of uterine torsion was worked out from the last ten year’s records, 2012-21, maintained at the Veterinary Clinical Complex of the institute. The overall incidence of uterine torsion was 14.17 %, with a higher occurrence in pluriparous (63.89%) compared to primiparous goats (36.11%). The majority of goats suffered from post-cervical torsion (77.78%) than that of pre-cervical torsion (22.22%), whereas the degree of torsion, <180 and >180 vis-a-vis direction of uterine rotation either to the right or left, distributed equally. Goat-carried single kids (97.22%) had significantly (P<0.01) higher incidences of uterine torsion than carried twins (2.78%). From the present study, it is concluded that uterine torsion prevailed in 14.17 % of goats to cause dystocia and was abundant post-cervical in a location with higher incidence associated with singleton pregnancies.